IMPLEMENTASI MULTIMEDIA-PEMBELAJARAN IPA BIOLOGI MODEL PBL UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Meike Paat; Yohanes Bery Mokalu; Ester Caroline Wowor; Widya Anjelia Tumewu; Rillya Arundaa (LPPM Politeknik Saint Paul Sorong, 2023)
The research aims to improve the learning outcomes of grade 9.7 students of Manado 7 Public Middle School through the implementation of problem based learning multimedia learning models. The lack ability of students to think, understand, and solve problems, exacerbated by the situation after the Covid-19 pandemic resulted in disrupted learning activities, so learning multimedia is needed that can optimize learning outcomes and facilitate the learning process. Using the classroom action research method, the research subjects were 34 students. Conducted in two cycles with four stages: planning, action, observation, and reflection. Data were analyzed using the formula P=????/????x100%. The results of the analysis show an increase in learning outcomes, as well as the ability to solve problems. This increase can be seen from the increase in classical completeness in each cycle, from an average of 65 cycles I to 82 in cycle II. Increasing the percentage of learning outcomes is 26%. The number of students fulfilling the minimum completeness criteria is 67% or 23 students (cycle I), to 94% or 32 students (cycle II). Student completeness from cycle I to cycle II increased by 27%.